Теорія інформації та системи безпровідного зв'язку - Серков, Олександр Анатолійович; Трубчанінова, Карина Артурівна; Касілов, Олег Вікторович; Лисечко, Володимир Петрович (Український державний університет залізничного транспорту, 2023)
Проведено аналіз властивостей інформації та визначено основні етапи її життєвого циклу. Рекомендовано підвищувати ефективність цифрових систем безпровідного зв’язку шляхом збільшення інформаційної ємності сигналу, використовуючи технологію надширокосмугового зв’язку. Розширення бази інформаційного сигналу слід здійснювати за рахунок одночасного кодування, модуляції та синхронізації інформаційного біта. Рекомендовано порівняльний аналіз інформаційних систем здійснювати з використанням інтегрального показника інформаційної ефективності, складовими якого є показники енергетичної та частотної ефективності.

An analysis of information properties was carried out and the main stages of its life cycle were determined. It is recommended to increase the efficiency of digital wireless communication systems by increasing the information capacity of the signal using ultra-broadband communication technology. Ultra-broadband signals are the most suitable for solving practical problems in the organization of wireless communication. It is shown that the use of technology of ultra-broadband signals allows wireless hidden transmission of information with low radiation power. Therefore, the efficiency of digital communication systems is significantly increased due to the creation of a complex signal ensemble by simultaneous coding, modulation and synchronization of an information bit, which expands its information base, while ensuring stealth and energy efficiency in a binary symmetric channel. The time distribution of the sync pulse and the information signal within the duration of the information bit makes it possible to guarantee the requirements of immunity, stealth and security of wireless communication channels due to the transmission of information by signals with low radiation power. A large signal base ensures stable, trouble-free operation of the digital information communication system even when the level of the information signal is below the noise level. However, the evaluation of the effectiveness of information systems requires the application of appropriate criteria. It is recommended to carry out a comparative analysis of information systems using an integral indicator of information efficiency, the components of which are indicators of energy and frequency efficiency.
Information theory and wireless communication systems
Keywords: властивості інформації; ентропія; ефективність інформаційної системи; критерій ефективності; information properties; entropy; information system efficiency; efficiency criteria